RESPON PERTUMBUHAN BEBERAPA AKSESI TANAMAN JARAK PAGAR (Jatropha curcas L.) TERHADAP PUPUK HAYATI SELAMA PEMBIBITAN - Ahmad Bashri (Universitas Sebelas Maret, 2013)
Physic nut (Jatropha curcas L.) is a potential plant for biofuels production. The objectives of this study was to analyze seedling growth response to application of biofertilizer during seedling establishment. The experiment were carried out in green house used Block Randomized Design with two factor and three replication. The first factor was four plant accessions i.e S1, J2, JB, and B3. The second factor was fertilizer treatment i.e with and without NPK at recommended rate, 36 g of AMF, and 30 g of PGPR. The result of this experiment indicated that the AMF and PGPR application increased vegetative growth and nutrient uptake of physic nut seedling. Key words: Jatropha Curcas L., Biofertilizer